Filial Piety: From the Perspective of Indonesian Young Adults - Setiyani, Rahmi; Windsor, Carol (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: Filial piety refers to expectations for children to respect parents and fulfill care responsibility, including provide direct care and support them in their old age. However, socio-demographic changes might shape how young generation would see and practice the value of filial responsibility in parent’s old age.Purpose: This study aimed to explore the meaning of filial responsibility among young adults within the social context of Indonesia.Methods: Symbolic interactionism formed the framework for this study. The constructivist grounded theory method guided the analysis of the data obtained from in-depth interviews with eight university students. The participants were selected using a purposive and snowball sampling technique with the following criteria: 18 years old or over, currently enrolled as a student and had living parents. Results: The result showed that redefining the meaning of filial responsibility was obtained as the main theme which linked all four categories: ‘I am the one’, ‘not institutional care’, ‘the gendering of caregiving’, and ‘it is okay to do so’. The findings revealed that the value of filial responsibility was still upheld by Indonesian young people. However, their views had been changed somewhat from the traditional practices which were family oriented and highly gendered to a more contemporary form where caregiving was extended to non-family caregivers and supposed to be less gendered in the practice.Conclusion: This study offers an insight into the shifting patterns in elderly caregiving and support in Indonesia. The findings also indicate the need to further promote gender equality in elderly caregiving.